Pengaruh Islamic Financial Literacy, Mental Accounting, dan Subjective Norm terhadap Perilaku Pengelolaan Keuangan Mahasiswa KIP Kuliah dengan Locus Of Control Sebagai Variabel Intervening - Zhella Annisa Annisa; Rachma Indrarini (Jurnal Ekonomika dan Bisnis Islam, 2025)
Financial management issues among university students often arise due to limited financial literacy, weak self-control, and a social environment that does not fully support healthy financial behavior. This becomes even more crucial for KIP-K scholarship recipients, who are required to manage their educational aid funds wisely and in accordance with Islamic principles. This study aims to examine the influence of Islamic financial literacy, mental accounting, and subjective norm on the financial management behavior of Muslim students receiving the KIP-K scholarship at the Faculty of Economics and Business, Universitas Negeri Surabaya, with Locus of control as a mediating variable. A quantitative approach was employed, involving 256 respondents and analyzed using the SEM-PLS method. The results indicate that all independent variables have a positive and significant effect on both financial management behavior and Locus of control. Furthermore, Locus of control significantly mediates the relationship between the three independent variables and financial behavior. These findings suggest that Muslim KIP-K scholarship recipients at FEB UNESA tend to demonstrate sound financial management behavior, characterized by careful financial planning, strong self-control, and adherence to Islamic financial principles.